Jack L. Davis (with contributions by Sharon R. Stocker). A Greek State In Formation. The Origins of Civilization in Mycenaean Pylos. - Dickinson, Oliver (Journal of Greek Archaeology, 2023)
pp. xxxiv+127, f 38 figures (17 colour), 8 maps (2 colour). (Sather Classical Lectures 75). Oakland: University of California Press, 2022. ISBN 9780520387249 (paperback), 9780520387259 (ebook). £27.